1999
DOI: 10.1017/s002531549900137x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the covering reaction of the purple sea urchin, Paracentrotus lividus, under laboratory and field conditions

Abstract: Abiotic and biotic aspects of the covering behaviour of the purple sea urchin, Paracentrotus lividus (Echinodermata: Echinoidea) were systematically examined in situ and in the laboratory to analyse potential intra-population differences in the nature of this behaviour. In the field, significant differences in the occurrence of covering behaviour were found between age groups. Smaller P. lividus covered at higher frequencies than larger individuals. Higher proportions of individuals were also observed to cover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
2
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 15 publications
2
26
2
4
Order By: Relevance
“…Elsewhere on the French Mediterranean coast, M. glacialis has been shown to carry out such feeding raids on the echinoid Paracentrotus lividus, which is estimated to constitute 50% of the diet of M. glacialis (Savy, 1987). A large population of P. lividus is resident amongst the boulder scree at 0^1m at all three of our study sites at Lough Hyne, and it has been the subject of several previous studies (Crook et al, 1999;Crook & Barnes, 2001). Ebling et al (1966) hypothesized that the unusual diurnally active nature of P. lividus at Lough Hyne (where sea urchins migrate to the tops of boulders during the day and below boulders at night) had evolved as a mechanism to avoid predation by nocturnally active M. glacialis.…”
Section: Discussionmentioning
confidence: 92%
“…Elsewhere on the French Mediterranean coast, M. glacialis has been shown to carry out such feeding raids on the echinoid Paracentrotus lividus, which is estimated to constitute 50% of the diet of M. glacialis (Savy, 1987). A large population of P. lividus is resident amongst the boulder scree at 0^1m at all three of our study sites at Lough Hyne, and it has been the subject of several previous studies (Crook et al, 1999;Crook & Barnes, 2001). Ebling et al (1966) hypothesized that the unusual diurnally active nature of P. lividus at Lough Hyne (where sea urchins migrate to the tops of boulders during the day and below boulders at night) had evolved as a mechanism to avoid predation by nocturnally active M. glacialis.…”
Section: Discussionmentioning
confidence: 92%
“…The behavioural ecology of P. lividus is known to follow circadian patterns with respect to migration (Ebling et al , 1966; Crook et al ., 2000) and covering behaviour (Crook et al ., 1999). Circadian patterns of activity have also been documented in P. lividus elsewhere (Dance, 1987) but also in many other tropical echinoid species (Thorton, 1956; Nelson & Vance, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of individuals covering and mean number of items used during the midday period were highest during summer. Thus both the daily (Crook et al ., 1999) and seasonal patterns of this behaviour seem linked to light climate either directly or indirectly.…”
Section: Discussionmentioning
confidence: 99%
“…Recently there has been an emphasis on studying specific behaviours, most notably ‘covering behaviour’, for example in the temperate echinoids Paracentrotus lividus and Strongylocentrotus droebachiensis . These studies have revealed complex relationships between covering and a number of biotic and abiotic factors (Crook et al. , 1999; Adams, 2001; Barnes & Crook, 2001).…”
Section: Problemmentioning
confidence: 99%
“…Covering behaviour in echinoids, otherwise referred to as ‘masking’, ‘hatting’ or ‘heaping’ behaviour, is characterized by individuals using their tube feet and spines to lift items onto their upper (aboral) surface (Millott, 1956, 1975). Items may include small stones, empty mollusc shells and algal fragments, amongst others (Crook et al. , 1999; Adams, 2001; Verling et al.…”
Section: Problemmentioning
confidence: 99%